CHANGES IN MORPHOMETRIC INDICES OF GASTRIC MUCOSA OF SEXUALLY MATURE RATS DURING ADMINISTRATION OF ENERGY DRINK WITH ALCOHOL IN DIFFERENT MODES OF PHYSICAL ACTIVITY - Xusanova Erkin Uktamovich; Suponova Kholida Sukhrobovna (Scholar Express Journals, 2024)
Nowadays, energy drinks occupy one of the leading places in many countries of the world in terms of frequency of consumption. Discussions about the harm or benefit of energy drinks are being conducted by scientists with increasing frequency. It is proved that energy drinks have a negative effect on some organs and systems, but their influence on the gastrointestinal tract is not sufficiently studied. It is of great practical interest to study the complex influence of energy drinks on the gastrointestinal tract, and, in particular, on the stomach at regular, long-term use of energy drinks, as well as at their use against the background of physical activity.
Keywords: stomach; morphology; energy drink; physical load